Identifying and prioritizing strategies to achieve scientific supremacy in one of the universities in northwest Iran - Sahar Valimoghadam Zanjani; Shohreh Mohebbi (Zanjan University of Medical Sciences and Health Services, 2023)
Background & Objective: The improvement of Iran's position as a developed country requires the enhancement of the efficiency of the scientific, research, and technological systems. Accordingly, universities must identify and determine the differentiation extent of their academic mission. This study aimed to determine the implementation of scientific supremacy strategies considering its differentiation extent in one of the universities in northwest Iran. Materials & Methods: This study was conducted based on an exploratory mixed method. SWOT (Strengths, Weaknesses, Opportunities, and Threats)-QSPM (Quantitative Strategic Planning Matrix) technique was used in order to determine the strategies to achieve supremacy. The internal and external factors at the university were identified through semi-structured interviews with 10 academic experts up to data saturation. A questionnaire was then designed and provided to 40 faculty members in order to score the factors. In addition, the QSPM technique was used to evaluate and prioritize the selected strategies. Results: SWOT matrix analysis led to the identification of 34 factors. The final scores of the internal and external factors were estimated at 2.29 and 2.03, respectively. As a result, the university under study was placed in the WT (weaknesses and threats) zone. According to the QSPM matrix, the prioritized strategies were communication and interaction at different levels, development of human resources, development of financial resources, compilation of related documents, and establishment of rules. Conclusion: According to SWOT analysis, the most important strategies to achieve scientific supremacy regarding university excellence are reinforcement of the strengths and exploitation opportunities by providing financial and human resources, establishing rules, and making comprehensive communication and interaction.